2012
DOI: 10.2174/1874210601206010164
|View full text |Cite
|
Sign up to set email alerts
|

Postextraction Implant Placement with Immediate Provisionalisation and Finalisation, Using a Simplified Technique: Technical Notes and a Case Report

Abstract: Trauma of maxillary teeth is a common accident. In most cases, the result is a root or crown fracture requiring tooth extraction and implant placement. Immediate postextraction implants are considered an effective option for restoring missing teeth in order to achieve successful aesthetic and functional outcomes. The aim of this article is to describe a clinical case in which a fractured maxillary canine was replaced by an osseointegrated implant using a simplified technique in a patient who was a smoker and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…This technique was easier, cheaper and faster than other techniques. This technique comes in agreement with recent researches (16) .…”
Section: Discussionsupporting
confidence: 92%
“…This technique was easier, cheaper and faster than other techniques. This technique comes in agreement with recent researches (16) .…”
Section: Discussionsupporting
confidence: 92%
“…16 This approach is generally indicated for specific patients such as those who demand esthetic treatments, implants placed in esthetic areas, 17,18 fractured teeth, 18 endodontic failures, nonrestorable caries, and radicular caries. 19 In these cases, the periodontal tissue should be healthy prior to implant placement. Soft tissue dehiscence and fenestrations are considered as contraindication for flapless implant insertion.…”
Section: [ E P U B a H E A D O F P R I N T ]mentioning
confidence: 99%
“…Soft tissue dehiscence and fenestrations are considered as contraindication for flapless implant insertion. 19 Implant treatment outcomes by flapless approach have been reviewed previously. 20-22 A review of 13 studies revealed that flapless technique results in 97.2% survival rate of dental implants and a mean 1.45mm marginal bone loss during 1-4 years of follow up.…”
Section: [ E P U B a H E A D O F P R I N T ]mentioning
confidence: 99%
“…Osseointegration is the primary biological and biophysical process by which dental implant therapy is predictably effective in replacing missing teeth (2) . In implantology, the concept of osseointegration was first introduced by Brånemark in 1964, and the guidelines for a direct connection between bone and titanium were described by the same author (3) .…”
Section: Introductionmentioning
confidence: 99%